2019
DOI: 10.1111/ajpy.12247
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well‐being and gender‐typed attributes in adolescents: The relevance of emotional intelligence

Abstract: Background: The link between subjective well-being (SWB), gender and emotional intelligence (EI) has been studied; however, it is not clear what kind of relationship has been established between these variables. The objective of this study was to examine the direct and indirect effects of EI in the relationship between gendertyped attributes and SWB. Method: The participants were 365 Spanish schoolchildren with a mean age of 13.9. The instruments used were the Spanish version of GRI-JUG (GRI-JUG-SP15) for gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…On the one hand, the results showed that high levels of selfefficacy would be related to low levels of perceived stress, in consonance with previous studies (Karademas and Kalantzi-Azizi, 2004;Zhao et al, 2015;Dominguez-Lara, 2018) and thus confirming hypothesis 2. On the other hand, the components of EI should be taken into account separately, since it has been seen that higher levels of EA were positively related to perceived stress, following the line of previous studies (Guerra-Bustamante et al, 2019;Martínez-Marín and Martínez, 2019) and supporting hypothesis 1 (Davis and Nichols, 2016;Villanueva et al, 2017). Otherwise, as indicated by previous studies (Bryant and Malone, 2015;Perera and DiGiacomo, 2015;Schönfeld et al, 2016;Zeidner and Matthews, 2016), EC was positively related to perceived stress, but ER did not do as expected, which partially supports hypothesis 1 (the greater the repair and EC, the lower the level of stress).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…On the one hand, the results showed that high levels of selfefficacy would be related to low levels of perceived stress, in consonance with previous studies (Karademas and Kalantzi-Azizi, 2004;Zhao et al, 2015;Dominguez-Lara, 2018) and thus confirming hypothesis 2. On the other hand, the components of EI should be taken into account separately, since it has been seen that higher levels of EA were positively related to perceived stress, following the line of previous studies (Guerra-Bustamante et al, 2019;Martínez-Marín and Martínez, 2019) and supporting hypothesis 1 (Davis and Nichols, 2016;Villanueva et al, 2017). Otherwise, as indicated by previous studies (Bryant and Malone, 2015;Perera and DiGiacomo, 2015;Schönfeld et al, 2016;Zeidner and Matthews, 2016), EC was positively related to perceived stress, but ER did not do as expected, which partially supports hypothesis 1 (the greater the repair and EC, the lower the level of stress).…”
Section: Discussionsupporting
confidence: 68%
“…A person with high expectations of selfefficacy, high scores on ER and clarity, and moderate scores on attention is associated with lower levels of perceived stress. Thus, the student will make a secondary assessment of the situation, and she will have healthy coping strategies that will allow her to reduce her stress levels (Martínez-Marín and Martínez, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results show that men score better in terms of self-esteem, happiness and affect, which agrees with recent studies that suggest that men have a greater ability to recognise and regulate their emotions. 28,29 These results may be related to men's tendency to agree with positive self-statements, reflecting unconscious dispositions towards the self. 30 Women, however, scored better in terms of subjective happiness, in contrast with recent studies that did not detect significant gender differences in this variable, 31 which confirms how difficult it is to reach conclusive results in this field.…”
Section: Discussionmentioning
confidence: 96%